PENGEMBANGAN SUBAL SUNGGAR PADA SANGGUL UKEL TEKUK ADAT YOGYAKARTA UNTUK SEMUA BENTUK WAJAH - Putra, Eka Sulistya; Wening, Sri (Jurnal Tata Rias, 2025)
The Yogyakarta traditional ukel tekuk bun is an important part of traditional make-up, with the sunggar supported by a subal to maintain its stability and shape. However, the materials and techniques for making traditional subal are considered less practical and comfortable, so innovation is needed to create a more modern subal without losing its traditional essence. This study aims to (1) identify the stages of subal development for the Yogyakarta traditional ukel tekuk bun sunggar, and (2) evaluate the feasibility of the subal based on expert validation and user assessment. The research method uses a Research and Development (R&D) approach with the PPE (Planning, Production, Evaluation) model. The data collection instrument involves expert validation and user assessment using a Likert scale of 4. The results of the study show several main findings: (1) Problems faced by make-up artists and users include lack of skills in making sunggar, discomfort of sasakan, shape that does not suit the face, and a long time-consuming process. Therefore, a practical subal was developed using materials such as hair, combs, needles, sewing threads, and other supporting tools. (2) The development process includes design, production, and evaluation. (3) Expert validation results showed a feasibility percentage of 95.16% (average 3.81), and user assessment reached 98.02% (average 3.92), both in the feasibility category.